Long-Term Viability of U.S. Agriculture - Tweeten, Luther G.; Braden, John B.; Fraley, Robert T.; Gerber, John F.; Greene, Daryle E.; Havener, Robert D.; Hermanson, Peter; Hesterman, Oran B.; Hudson, William J.; Janssen, Gail E.; Jensen, James K.; Lacy, William B.; et al. (Council for Agricultural Science and Technology (CAST), 1988)
What is the future of American agriculture? This report examines the economic, environmental, and social dimensions of the agricultural sector.